Perancangan Media Presentasi Alternatif Menggunakan Focusky Pada Matakuliah Jaringan Komputer di Program Studi PTIK UIN Bukittinggi - Alya Zulda Putri; Hari Antoni Musril (UNIVED Press, 2023)
Abstract— The implemlelntation of computer network lectures in the delivery of learlning materials already uses media such as zoom meetings and pdf files. Basically there is nothing wrong in using the media. However, the authors argue that it would be better if it was comblined with the use of presentation medlia-based technology. Meanwhile students said that the material provided was quite understandable, but there was a feleling of bolredom during learning because the media was monotonous in the form of pdf files only, and the contents of each slide were too dense/many. Based on this, the solution given is to design a media presentation. Research on the deslign of preselntation media using focusky on computer network courses at the PTIK IAIN Bukittinggi study program uses the Research and Development (R&D) method with the DDD-E development model. Media development using the DDD-E model consists of (1) Decide or set progrlam goals and materials, (2) Design or design, namely creating program structures, (3) Develop or developing is prolducing media elements and making media appearance, (4) Evaluate or evaluate, namely checking the entire design and development process. The product tests used in this study are validity tests, practicality tests, and effectiveness tests. The results of the product test that the author did obtained a validity test from 4 validlators obtained a value of 0.85 with a very valid category, a practiclality test from 3 practicators obtained a value of 0.94 with a very high category, and the effectiveness test from 31 assessors obtained a value of 0, 88 with very effectlive category. Keyword: Presentaltion Media, Foclusky, Research and Development (R&D)